Intron mutations and early transcription termination in Duchenne and Becker muscular dystrophy. Issue 4 (7th March 2022) - Waldrop, Megan A.; Moore, Steven A.; Mathews, Katherine D.; Darbro, Benjamin W.; Medne, Livja; Finkel, Richard; Connolly, Anne M.; Crawford, Thomas O.; Drachman, Daniel; Wein, Nicolas; Habib, Ali A.; Krzesniak‐Swinarska, Monika A.; et al.
Abstract: DMD pathogenic variants for Duchenne and Becker muscular dystrophy are detectable with high sensitivity by standard clinical exome analyses of genomic DNA. However, up to 7% of DMD mutations are deep intronic and analysis of muscle‐derived RNA is an important diagnostic step for patients who have negative genomic testing but abnormal dystrophin expression in muscle. In this study, muscle biopsies were evaluated from 19 patients with clinical features of a dystrophinopathy, but negative clinical DMD mutation analysis. Reverse transcription‐polymerase chain reaction or high‐throughput RNA sequencing methods identified 19 mutations with one of three pathogenic pseudoexon types: deep intronic point mutations, deletions or insertions, and translocations. In association with point mutations creating intronic splice acceptor sites, we observed the first examples of DMD pseudo 3ʹ‐terminal exon mutations causing high efficiency transcription termination within introns. This connection between splicing and premature transcription termination is reminiscent of U1 snRNP‐mediating telescripting in sustaining RNA polymerase II elongation across large genes, such as DMD . We propose a novel classification of three distinct types of mutations identifiable by muscle RNA analysis, each of which differ in potential treatment approaches. Recognition and appropriate characterization may lead to therapies directed toward full‐length dystrophin expression for some patients. Abstract : Intron mutations include the novel mechanism of pseudo‐3'UTR creation, confirmed by RNA Seq.